Religious faith and heterosexuality: a multi-faith exploration of young adults - Yip, Andrew Kam-Tuck; Page, Sarah-Jane (Brill, 2014)
This paper examines the understandings and practices of 515 heterosexual religious young adults living in the UK in terms of their religious faith and sexuality. It presents qualitative and quantitative data drawn from uestionnaires, interviews, and video diaries. Four themes are explored. First, participants generally understood sexuality in relation to sacred discourses. Second, regardless of gender and religious identification, the participants drew from religious (e.g. religious community) and social (i.e. friends) influences to construct their sexual values and attitudes. Third, the religious and familial spaces within which the participants inhabited were structured by heteronormative assumptions. Thus, the participants must negotiate dominant norms, particularly those pertaining to marriage and sex within it. Finally, the paper focuses on married participants, offering insights into their motivations for, and experiences of, marriage. Overall, the paper demonstrates that, like their lesbian and gay counterparts, heterosexual religious young adults also had to manage various competing and mutually-reinforcing sexual and religious norms in constructing a meaningful life.